2017
DOI: 10.1140/epjp/i2017-11647-9
|View full text |Cite
|
Sign up to set email alerts
|

GIARPS@TNG: GIANO-B and HARPS-N together for a wider wavelength range spectroscopy

Abstract: Since 2012, thanks to the installation of the high resolution echelle spectrograph in the optical range HARPS-N, the Italian telescope TNG (La Palma) became one of the key facilities for the study of the extrasolar planets. In 2014 TNG also offered GIANO to the scientific community, providing a near-infrared (NIR) cross-dispersed echelle spectroscopy covering 0.97 − 2.45 µm at a resolution of 50,000. GIANO, although designed for direct light-feed from the telescope at the Nasmyth-B focus, was provisionally mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 36 publications
(32 reference statements)
0
52
0
Order By: Relevance
“…This would further unveil features and regions that were indistinguishable earlier. This will particularly hold true as the M dwarf M-R space starts to fill up with radii from TESS (Thibault et al 2012), IRD (Kotani et al 2018), ESPRESSO (Hernndez et al 2017), NIRPS (Wildi et al 2017), SPIRou (Artigau et al 2014), iSHELL (Cale et al 2018), GIANO (Claudi et al 2017) and EXPRES (Jurgenson et al 2016).…”
Section: Future Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…This would further unveil features and regions that were indistinguishable earlier. This will particularly hold true as the M dwarf M-R space starts to fill up with radii from TESS (Thibault et al 2012), IRD (Kotani et al 2018), ESPRESSO (Hernndez et al 2017), NIRPS (Wildi et al 2017), SPIRou (Artigau et al 2014), iSHELL (Cale et al 2018), GIANO (Claudi et al 2017) and EXPRES (Jurgenson et al 2016).…”
Section: Future Prospectsmentioning
confidence: 99%
“…It has also been shown that the spot-induced RV jitter is reduced in the near infrared (NIR) (Marchwinski et al 2015), which is where the spectral energy distributions for these stars peak. For these reasons, many more M dwarf planets will have their masses measured in the near future by instruments such as the HPF (Mahadevan et al 2012), CARMENES (Quirrenbach et al 2016), NIRPS (Wildi et al 2017), IRD (Kotani et al 2018), SPIRou (Artigau et al 2014), iSHELL (Cale et al 2018), GIANO (Claudi et al 2017), and NEID (Schwab et al 2016). Here we set the stage for these future datasets by assessing the dependence of the M-R model choices on mass and radius predictions, especially as a function of stellar type.…”
Section: Introductionmentioning
confidence: 99%
“…Instruments such as CARMENES (Quirrenbach et al 2016) and GIARPS (GIANO-B+HARPS-N, Claudi et al 2017) minimize the stellar activity problem by obtaining simultaneous optical (VIS) and near-infrared (NIR) data. The RV signal of planetary origin is independent of the observed wavelength, whereas the amplitude of the signal due to stellar activity may strongly depend on wavelength (typically larger at shorter wavelengths; e.g., Martín et al 2006;Huélamo et al 2008;Carleo et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Observing PMS stars in the near infrared (nIR) rather than in the V band should make it easier to separate the E-mail: baptiste.klein@irap.omp.eu planet signature from the stellar activity signal as the latter is expected to be weaker in this domain (Mahmud et al 2011) and the stars are significantly reddened. Highprecision nIR velocimeters like SPIRou (Donati et al 2018), CARMENES (Quirrenbach et al 2014), GIARPS (Claudi et al 2017) or NIRPS (Wildi et al 2017) are thus the most promising instruments worldwide to carry out mass measurements of close-in transiting planets orbiting PMS stars. Magnetic fields are however expected to affect stellar RV activity signals (Reiners et al 2013;Hébrard et al 2014), making the problem non trivial and worth a detailed simulation study.…”
Section: Introductionmentioning
confidence: 99%